Examination of the Claims of Distortion on the Qur’?n which is in al-Qumm? Commentary - Saylan, Nesrişah (My University, 2018)
In this study, the distortion of claims on the text of the Qur’?n in Tafs?r al-Qumm? which is one of the main sources of Sh?‘a has been investigated. al- Qumm?, the first scholar of the Shi’ite scholars, claims that in the account of the commentary are distorted in the text of the Qur’?n with various subtitles, such as the verses that are in the land of Allah's descendants and distorted verses. While interpreting the verses, he discloses this claim in detail and sometimes gives the correct shapes of the revelations as the difference of interpretation, sometimes based on the narrations, and sometimes in the way of reading the verse. In this study, the verses alleged to be literally distorted in his commentary have been determined and this claim has been compared with other commentaries. The purpose of the article in this context is; in the case of al-Qumm? exegesis, it is the examination of the verses allegedly distorted in the Qur’?n and the determination of the Sh?‘? commentators based on the doctrine of sects by changing the text of the Qur’?n.
Keywords: Din Bilimi; Beşeri Bilimler